Development Needs Analysis Science Literacy Assessment Instruments Matchup Type Wordwall Based Earth Change Materials - Sahmanita, Riqqah Salsabila; Wasino, Wasino; Sutopo, Yeri; Lestari, Wahyu; Setiawan, Deni (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
Developing scientific literacy assessment instruments on earth change material for elementary school students is important. The development of scientific literacy-based assessment instruments is an effort to measure students' scientific literacy abilities. The research aims to develop a creative and innovative assessment instrument, namely matchup. Initial research was used to capture the needs for scientific literacy assessment instruments needed by teachers and students. The needs analysis research method uses qualitative research to collect initial data. Data collection techniques used range from observation, interviews, and documentation. The data is analyzed interactively and effectiveness tests are carried out to obtain the empirical benefits of the tool in the field. Research development on the products produced is done through expert judgment by instrument experts, media experts, and stakeholders (teachers as users). The research showed that the matchup game was very effective in carrying out science learning evaluations. Product analysis is very effectively used in assessment activities in science learning for elementary school students, especially in material regarding changes in the earth caused by humans.